The Pursuit of Social, Economic, and Environmental Justice through Evaluation: Learning from Indigenous Scholars and the Fifth Branch of the Evaluation Theory Tree - Donna Mertens (The Evaluation Center at Western Michigan University, 2023)
The world faces a climate crisis that calls for increased attention to social, economic, and environmental justice. Non-Indigenous evaluators can choose to continue their work business-as-usual, or they can choose to learn from Indigenous evaluators. The exclusion of Indigenous scholars from the evaluation theory tree results in an opportunity lost to improve theory and practice across all communities. A fifth branch on the evaluation theory tree, Context and Needs, aligns with the Indigenous paradigm and serves to stimulate questions about evaluation theory and practice that inherently address issues of justice and the importance of recognizing the interconnectedness of all living and nonliving things.